2012
DOI: 10.1002/nau.22214
|View full text |Cite
|
Sign up to set email alerts
|

How should bladder sensation be measured?: ICI‐RS 2011

Abstract: AimsDisturbed bladder sensations, or in broader terms, sensory dysfunctions are increasingly recognized as key elements in the origin and manifestation of symptom syndromes of urinary dysfunction. Adequate assessment of bladder sensation is crucial to improve our understanding of the pathophysiology and treatment of urinary dysfunction. This manuscript summarizes the discussions of a think tank on “How to measure bladder sensation” held at the ICI‐RS meeting in 2011.MethodsBased upon literature reviews on blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Bladder sensation can be generated by physiological (sensation of bladder filling, urge or the desire to void, and sensation during micturition), and pathologic (urgency and pain) processes . The current established description of three episodic sensations—(i) first sensation of filling; (ii) first desire to void described as a constant sensation gradually becoming more intense; and (iii) strong desire to void, a constant localized sensation to the perineal region or the urethra to void—does not reconcile with the theory that progressive increase in afferent information and constantly growing sensations occurs with progressive bladder filling at a constant rate . Further, these symptoms are poor discriminators of physiology versus pathology.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Bladder sensation can be generated by physiological (sensation of bladder filling, urge or the desire to void, and sensation during micturition), and pathologic (urgency and pain) processes . The current established description of three episodic sensations—(i) first sensation of filling; (ii) first desire to void described as a constant sensation gradually becoming more intense; and (iii) strong desire to void, a constant localized sensation to the perineal region or the urethra to void—does not reconcile with the theory that progressive increase in afferent information and constantly growing sensations occurs with progressive bladder filling at a constant rate . Further, these symptoms are poor discriminators of physiology versus pathology.…”
Section: Introductionmentioning
confidence: 82%
“…The bladder sensation‐logging tool used in this study employed a water loading protocol, which achieves a high diuresis with rapid, non‐invasive bladder filling . It is a simple and non‐invasive approach to identifying, recording, and quantifying sensation associated with bladder filling and voiding, based on subjective interpretation without relying on the use of pre‐determined terminology from the researcher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tension-sensitive afferent nerves in the bladder wall convey fullness sensation to the brain (Morrison, 1999), while bladder compliance affects the tension sensor load during filling (De Wachter et al, 2012). Bladder compliance has been shown to depend on shape (Damaser and Lehman, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, participants in a study by Heeringa et al reported sensation induced by forced diuresis (focal period “right now”). It is possible that sensation generated by rapid bladder filling differs from usual sensation . Furthermore, participants in the study by Heeringa et al were required to wait until their bladders were full before voiding and “tingling” described sensation experienced in the perineal region when the bladder was very full.…”
Section: Discussionmentioning
confidence: 99%